Total enthalpy-based lattice Boltzmann simulations of melting in paraffin/metal foam composite phase change materials. (July 2020) - Gaedtke, Maximilian; Abishek, S.; Mead-Hunter, Ryan; King, Andrew J. C.; Mullins, Benjamin J.; Nirschl, Hermann; Krause, Mathias J.
Highlights: Two relaxation time (TRT) lattice Boltzmann method (LBM) for the simulation of melting and conjugate heat transfer in 2D and 3D. Superlinear grid convergence and close agreement for a large range of lattice relaxation times and Stefan numbers. Interfacial diffusion is effectively limited by choosing the TRT's "magic parameter" to 1/4. Melting of paraffin in two complex metal foam geometries is successfully described, where the thermal conductivity of the foam is more than 1000 times larger than that of the paraffin. Abstract: Phase change materials (PCM) have become a popular choice for building thermal management due to their low cost, chemical stability and high energy density. Though, their low thermal conductivity is a limiting factor in their use. To overcome this limitation, there has been considerable interest in the application of highly conductive substrates such as metal foams. These offer a potential to increase the thermal performance of PCM and to broaden their area of application. However, the influence of micro structured properties on melting is not completely understood and difficult to explore experimentally. In this study, a lattice Boltzmann method (LBM) based on the two relaxation time (TRT) collision scheme for the simulation of melting and conjugate heat transfer is proposed, validated and applied to melting in three-dimensional (3D) structures of composite PCM-metal foam latent heat storages. The model and its implementation is validated against the analytical transient solution of the Stefan problem, proving superlinear grid convergence and close agreement for a large range of lattice relaxation times and Stefan numbers. The interfacial diffusion is found to be effectively limited by leveraging a TRT collision scheme. Very close accordance to measurements and simulation results obtained with other methods is shown for the validation case of melting gallium including natural convection in 2D and 3D. Subsequently, the melting of paraffin in two complex metal foam geometries is simulated. The present simulations successfully describe the multi-domain heat transfer in 3D, where the thermal conductivity of the foam is more than 1000 times larger than that of the paraffin. The predicted progression of the melting front and the influence of the different foam's specific surface area are in close agreement to earlier simulations.